Badanie pewnego estymatora prawdopodobieństwa ruiny - Kwaśniewska, Magdalena; Michna, Zbigniew (Analysis of a certain estimator of ruin probability, 2005)
In the paper we analyse a certain estimator of ruin probability in the risk model of good and bad periods and the probability of the buffer overflow which is the most important quantity in performance of high-speed telecommunication networks. We indicate an error in Piterbarg’s and Romanova’s article and investigate the second moment of this estimator. Finally, we present some numerical results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 318-325